2012
DOI: 10.1007/s12265-012-9436-x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Protects Human Endothelial Cells from H2O2 Oxidant Injury Through the Mek/Erk-Sirt1 Axis Activation

Abstract: Endothelium homeostasis alterations govern the pathogenesis of cardiovascular diseases. Several studies show that vitamins anti-oxidant proprieties rescue the endothelial functions adversely affected by oxidative stress in several diseases. We investigated the vitamin D anti-oxidant potential in human endothelial cells exposed to H2O2 oxidative stress. Vitamin D protected endothelial cells against H2O2 oxidative stress counteracting the superoxide anion generation, the apoptosis and blocking the extrinsic casp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(101 citation statements)
references
References 48 publications
5
93
1
1
Order By: Relevance
“…These results agree with those published in previous reports showing that cAMP increases inhibitory Raf-1 phosphorylation at Ser-259 and reduces activating Raf-1 phosphorylation at Ser-338 in a PKA-dependent manner, thereby inducing ERK deactivation (33,34). ERK activates SIRT1 in chondrocytes (35) and induces SIRT1 expression in human endothelial cells (36); however, the effect of ERK on SIRT6 remains unknown. The present study showed that inhibiting the Raf-MEK-ERK pathway also reduces SIRT6 expression in lung cancer cells.…”
Section: Discussionsupporting
confidence: 92%
“…These results agree with those published in previous reports showing that cAMP increases inhibitory Raf-1 phosphorylation at Ser-259 and reduces activating Raf-1 phosphorylation at Ser-338 in a PKA-dependent manner, thereby inducing ERK deactivation (33,34). ERK activates SIRT1 in chondrocytes (35) and induces SIRT1 expression in human endothelial cells (36); however, the effect of ERK on SIRT6 remains unknown. The present study showed that inhibiting the Raf-MEK-ERK pathway also reduces SIRT6 expression in lung cancer cells.…”
Section: Discussionsupporting
confidence: 92%
“…Bernier et al (22) reported negative regulation of STAT3 protein-mediated cellular respiration by SirT1 in murine embryonic fibroblast cells (21), and a previous study provided further support for these results (41). As previously demonstrated, pSTAT3 stimulated expression of the STAT3 gene [unphosphorylated STAT3 (U-STAT3)], which exerted persistent activity (42).…”
Section: A B C Dmentioning
confidence: 60%
“…Cells were incubated with H 2 O 2 (50 µM) for 24 h. Subsequently, H 2 O 2 was detoxified by the addition of catalase (100,000 µl; Worthington Biochemical Corp., Lakewood, NJ, USA) at the end of the incubation (22). oxLDL (200 µg/ml) was added to other samples to induce pathological stress in ARPE-19 cells following 24 h treatment (23).…”
Section: Analysis Of Intracellular Reactive Oxygen Species (Ros) Levelsmentioning
confidence: 99%
“…Recently, vitamin D has been indicated to exhibit anti-glycation [10,11,12] and anti-oxidation (oxidative stress is the final step of the Maillard reaction) effects [13,14]. In humans, there have been only two AGE studies using high-dosage vitamin D [10,12].…”
Section: Discussionmentioning
confidence: 99%